Prospects of Natural Zeolites in Indonesia for Industrial Separations and Environmental Management - Yateman Arryanto; Siti Amini; Max G. Q. Lu (Jurnal Zeolit Indonesia, 2002)
Zeolite as well as molecular sieves are a class of aluminosilicate materials, which have found wide use in industries for separation, purification and pollution control. In the new era of nanomaterials in the 21st century, these nanoporous materials have become more widely used in separation, catalysis and environmental management, even in microelectronic and energy storage sectors. The following briefly shows the great potential of natural zeolites for some important environmental applications: CO2 removal from landfill gas and coal seam gas using Pressure Swing Adsorption (PSA) with Clinoptilolites: Natural zeolite is not only a cheaper solution to the economical storage system of methane for NGVs but it also present a safer storage medium as alternative adsorbent such activated carbon is flammable and very costly. There is also an increasing interest in indoor air quality control issues among the building industries and health organizations. It has been demonstrated that clinoptilolite is particularly effective adsorbent for odours and some volatiles in indoor environment. Another area of importantnce of natural zeolites is the solar energy application. Zeolites can adsorb water vapour and create effective cooling with solar heat as the energy to regenerate the zeolite. Systems using zeolites can be designed in such a way that combined cooling and heating can be achieved at about 40-60% efficiency. Adsorption of Nitrogen and Oxygen in zeolites for PSA application Cp zeolite deposit has about 75% of the capacity of a commercial Mordenite zeolite for air separation at 30°C. The dynamics studies showed that Cp zeolite is suitable for N2 and O2 separation due to their large difference in adsorption kinetics.